2017
DOI: 10.18632/oncotarget.12574
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Epimedii Folium and Curculiginis Rhizoma on Alzheimer’s disease by the inhibitions of NF-κB/MAPK pathway and NLRP3 inflammasome

Abstract: The purpose of the current study was to explore the effects of the water extracts of Epimedii Folium and Curculiginis Rhizoma (EX) on Aβ-induced Alzheimer’s disease. Aβ1-42 was stereotaxically injected bilaterally into the dorsal hippocampus, and then the rats were orally received EX at the doses of 2 g/kg and 6 g/kg for 30 days. Behavior was monitored through Morris water maze test. The neuroprotective effect of EX were examined with methods of histochemistry and biochemistry. EX reduced the contents of pro-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 39 publications
4
17
0
Order By: Relevance
“…The major upstream mechanisms of NLRP3 inflammasome activation include ROS, phagosomal destabilization, and ion fluxes [ 45 ]. Ample evidence showed that high rate of ROS is produced in hyperglycemia, thereby affecting neurons [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major upstream mechanisms of NLRP3 inflammasome activation include ROS, phagosomal destabilization, and ion fluxes [ 45 ]. Ample evidence showed that high rate of ROS is produced in hyperglycemia, thereby affecting neurons [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that the NLRP3 inflammasome plays an important role in the molecular mechanism of diverse diseases [ 30 , 31 ]. Inhibition of NLRP3 inflammasome activation provides protective effects in renal fibrosis [ 32 ] and inflammatory bowel disease [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rhizoma Curculiginis (Xianmao in Chinese) is a commonly used drug in traditional Chinese medicine; its functions include tonifying kidney yang and improving blood supply [12,13].…”
Section: Introductionmentioning
confidence: 99%